From data to action: a scoping review of wearable technologies and biomechanical assessments informing injury prevention strategies in sport - Rebelo, A.; Martinho, D. V.; Valente-dos-Santos, J.; Coelho-e-Silva, M. J.; Teixeira, D. S. (BMC Sports Science, Medicine and Rehabilitation, 2023)
Background The purpose of this scoping review was to evaluate the current use of technologies in sports settings for training adaptation and injury prevention. The review aimed to map the existing literature, identify key concepts and themes, and highlight gaps in research, thus offering guidance for future studies.